Effect of Initial Temper on the Warm Forming Characteristics of a High Strength 7000-series Al-Zn-Mg-Cu Alloy. Issue 1 (1st May 2022) - DiCecco, S; Di Ciano, M; Butcher, C; Worswick, M
Abstract: In this work, the formability of a developmental 7000-series copper containing aluminium alloy was assessed at room temperature (RT), 150°C, 175°C and 200°C in pre-aged (PA), peak-aged (T6) and overaged (T76) tempers using Nakazima tests with stereoscopic digital image correlation (DIC) strain measurement. The limit strains were identified using a novel curvature-based approach to detect the formation of an acute neck. The tensile mechanical properties in these warm forming processing routes were characterized with and without a paint bake cycle. Finally, a thermo-mechanical tensile simulator was used to evaluate the constitutive response of the PA and T76 tempers as a function of strain-rate and time at 175°C. Formability results found the selected PA temper to have a good room temperature formability and a mild positive response to the selected warm-forming cycles. The T6 and T76 tempers both exhibited increases in formability in response to warm forming. The PA temper had a significant positive response to short-duration warm forming and subsequent paint baking, with the yield strength increasing from 420 MPa to 512 MPa following this thermal cycle. For the T6 temper, the warm-forming cycle showed a trend characteristic of retrogression and re-aging, with the warm-forming cycle dropping the yield strength from 566 MPa to 534 MPa and the subsequent paint-bake re-aging to 554 MPa. The effect of aging during pre-heating prior to warm forming on the warm constitutive response of the PA and T76 tempers was also investigated. Both tempers exhibited rather different aging responses to short-duration thermal cycles. In the PA temper, this manifested as an increase in at-temperature yield strength and loss of hardening rate. In contrast, the T76 temper exhibited a drop in strength since this temper is already over-aged prior to warm forming. Both the PA and T76 tempers showed comparable at-temperature strain-rate sensitivity.